Evolutionary Humanoid Robotics - Eaton, Malachy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book examines how two distinct strands of research on autonomous robots, evolutionary robotics and humanoid robot research, are converging. The book will be valuable for researchers and postgraduate students working in the areas of evolutionary robotics and bio-inspired computing.
Introduction -- Evolutionary Algorithms and the Control of Systems -- Evolutionary Robotics (ER) -- Humanoid Robots, Their Simulators, and the Reality Gap -- Evolutionary Humanoid Robotics (EHR) -- The State of the Art in EHR -- Performance Evaluation and Benchmarking of Humanoid Robots -- Ethical, Philosophical and Moral Considerations -- Conclusions, and the Future.
Keywords: Artificial intelligence; Engineering; Artificial Intelligence; Control, Robotics, Mechatronics; Computational Intelligence